Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.langmuir.8b01503
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of the Self-Assembly of Phospholipid Nanodiscs: What Determines Their Shape and Stoichiometry?

Abstract: Phospholipid nanodiscs have quickly become a widely used platform for studies of membrane proteins. However, the molecular self-assembly process that ultimately should place a membrane protein inside a nanodisc is not well understood. This poses a challenge for a successful high-yield reconstitution of general membrane proteins into nanodiscs. In the present work, the self-assembly process of POPC-MSP1D1 nanodiscs was carefully investigated by systematically modulating the reconstitution parameters and probing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 57 publications
6
38
0
Order By: Relevance
“…2c and 2d). This variation is ascribed to a small structural dispersity of the nanodiscs, with a variation in the lipid aggregation number as a function of retention volume, in line with other results from our group (Skar-Gislinge et al, 2018) and consistent with recently reported findings for MSP1E3D1 nanodiscs (Graziano et al, 2018). This structural effect would not have been visible without SEC-SAS.…”
Section: Benchmarking the Sec-sans Setup On Empty Nanodiscssupporting
confidence: 92%
“…2c and 2d). This variation is ascribed to a small structural dispersity of the nanodiscs, with a variation in the lipid aggregation number as a function of retention volume, in line with other results from our group (Skar-Gislinge et al, 2018) and consistent with recently reported findings for MSP1E3D1 nanodiscs (Graziano et al, 2018). This structural effect would not have been visible without SEC-SAS.…”
Section: Benchmarking the Sec-sans Setup On Empty Nanodiscssupporting
confidence: 92%
“…Importantly, the number of belt proteins and lipids derived from model fitting (2.08 and 135, respectively) were similar to expected values of 2 and roughly 150, respectively . It has been found that the stoichiometry of lipid incorporation in NLPs can vary across subfractions of an SEC peak, so the selective pooling of small portions of an SEC peak can result in slightly different lipid stoichiometry than what may be reported for less stringent fraction pooling.…”
Section: Discussionsupporting
confidence: 71%
“…It is well-known that double HC chain synthetic surfactants and phospholipids form bilayer structures in water above a very low cac value. [5][6][7][8][9][10] There are also reports on bilayer membrane formation by nonionic double-tailed surfactants which contain polyglyceryl as head group. 11 The growing interest on vesicular structures is largely because they have unique structure which can solubilize both hydrophilic and hydrophobic molecules within the aqueous core and bilayer membrane, respectively.…”
Section: Introductionmentioning
confidence: 99%